KINSHIP-BASED PROBLEMS AFFECTING THE EMPLOYEE PERFORMANCE: A STUDY CASE OF FAMILY BUSINESS IN DEVELOPING CITY IN INDONESIA - Zakia, Magfira Rahma; Pritasari, Adita (PEOPLE: International Journal of Social Sciences, 2018)
A family business is an organization in which maintains balance the professional management, responsible business ownership, and the healthy family dynamic (Wills D, 2017). The research is implemented in one of developing cities in Indonesia, a city which is famous of its traditional food. Therefore, the object of this research is one of traditional food companies who has successfully survived since 1957 which employs 277 workers in order to know the issues related with family which may affect the employees’ performance and understand the effective way to manage both family and non-family employee in family business. This research uses the semi-structured interview and non-participant observation method. The interview is conducted with six persons who two of them are representatives of non-family employee that have been working for more than 10 years and four of them are representatives of family employees who occupy the top management position. Meanwhile, the observation helps to see the discrepancy between what the family employees say and non-family employees feel. In comparison with common family businesses, this company also faces the common issues which are the nepotism, emotions interfere with the business, non-family member growth limitation, bad succession plan, lack of talent, and paternalistic issues. Most of the issues are related with each other. On the other hand, issues that particularly happen only in this family business are contract, tradition and religion, loyalty, and leadership issue. Those issues negatively affect most of employee performance. Therefore, the company needs to upgrade the Personnel Division into a Human Resources Division to solve issues related with performance of people within the company (Ulrich, 1997). A function of Human Resources Division is not only for the administration but also for company strategy to improve the employees’ performance by identifying the culture attributes of the company in order to make a succession plan.